Prognostic nutritional index and mortality in pneumonia: a retrospective cohort study in China - Ding, Zhengrong; He, Yunxue; Guo, Xue; Feng, Ruirui; Ren, Guangqin; Deng, Lili; Zhou, Chunjiao; Tang, Huali; Li, Zhiwei; Zhou, Cong; Li, Bin; Li, Longdan (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to investigate the association between prognostic nutritional index (PNI) and mortality risk in Chinese patients with pneumonia.MethodsThis retrospective cohort study was conducted using a multicenter hospital database of adult patients with pneumonia in China. We analyzed data from 635 patients diagnosed with pneumonia at six secondary and tertiary academic hospitals in China between 1 January 2013 and 31 December 2019. Cox regression analysis was used to compare the mortality rates across the PNI tertiles. Restricted cubic spline (RCS) models, Kaplan–Meier survival analysis and Subgroup Analysis were used to explore the association between PNI and the clinical outcomes of these pneumonia patients.ResultsA total of 635 patients were included. In the fully adjusted model, each 1-unit increase in PNI was associated with a 5.0% reduction in 30-day mortality risk (HR = 0.950, 95% CI: 0.929–0.972, p < 0.001) and a 4.5% reduction in 90-day mortality risk (HR = 0.955, 95% CI: 0.934–0.975, p < 0.001). Compared with the lowest PNI tertile (Tertile 1), patients in the highest tertile (Tertile 3) had a 64.5% lower risk of 30-day mortality (HR = 0.335, 95% CI: 0.212–0.594, p < 0.0001) and a 60.6% lower risk of 90-day mortality (HR = 0.394, 95% CI: 0.247–0.627, p < 0.0001). Restricted cubic spline (RCS) analysis further illustrated a consistent inverse relationship between PNI and mortality risk. Additionally, Kaplan–Meier survival curves indicated significantly lower cumulative mortality with higher PNI values.ConclusionOur investigation identified a significant association between poorer PNI scores and higher mortality in Chinese patients with pneumonia.